Presence of Klebsiella Pneumoniae on Black Hairy Tongue as Oral Microbiome Dysbiosis - Bakti, Reiska Kumala; Pradnyani , I Gusti Agung Sri; Subarnbhesaj, Ajiravudh; Radithia, Desiana (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Black hairy tongue (BHT) is a benign condition characterized by discoloration and elongation of filiform papillae. Although asymptomatic, it can trap microorganisms, potentially contributing to oral dysbiosis. The pathogenesis is still unclear, but smoking, drugs, alcohol, or excessive coffee/tea consumption trigger it. Diagnosis relies on history-taking, clinical assessment, and occasionally microscopic evaluation. This case report aims to show an interesting finding in the microbiological examination of black hairy tongue. Case: A 33-year-old male smoker and coffee drinker presented with black tongue discoloration. Any medication use and a history of systemic diseases are denied, but he had a habit of smoking, staying up late, and heavy coffee consumption. Case Management: Clinical assessment and microbiological swab analysis for bacterial and fungal identification were conducted. Microbiological examination revealed the presence of Klebsiella pneumoniae, a colonizing opportunistic pathogen. Discussion: The patient reported no systemic diseases or medication use, with lifestyle factors identified as potential triggers. This case underscores the role of lifestyle factors and oral hygiene in the development of BHT and its association with microbial dysbiosis. Conclusion: The detection of K. pneumoniae emphasizes the need for microbial evaluation in persistent cases to prevent potential systemic effects.